Immunogenetic markers in IL17F predict the risk of metastases spread and overall survival in rectal cancer patients treated with neoadjuvant chemoradiotherapy. (August 2020) - Cecchin, Erika; De Mattia, Elena; Dreussi, Eva; Montico, Marcella; Palazzari, Elisa; Navarria, Federico; Bergamo, Francesca; Belluco, Claudio; Quartuccio, Luca; De Vita, Salvatore; Canzonieri, Vincenzo; Gagno, Sara; et al.
Highlights: Patients immunogenetics can impact tumor response to radiotherapy. Unmet need of prognostic markers in locally advanced rectal cancer. Two immunogenetic prognostic markers in IL17F were identified. Tumor Regression Grade prognostic value is integrated by IL17F -rs641701 and IL17F- rs9463772. Additional stratification criteria for the selection of an organ sparing strategy. Abstract: Background and purpose: The role of the immune system in tumor response to chemo-radiotherapy (CRT) is an emerging issue. This work aimed at identifying predictive and prognostic immunogenetic variants in LARC patients after preoperative (po)-CRT and surgery. Materials and methods: A set of 192 polymorphisms in 34 candidate genes involved in the regulation of the immune response signalling network, was selected and analyzed in 370 LARC patients treated with po-CRT and surgery, split into a Test Set ( n  = 233) and a Validation Set ( n  = 137). Immunogenetic markers were selected based on a concordant significant effect on 2-year relapse-free survival (2-yrRFS) (bootstrapped P  < 0.05) in both patients Sets. The effect of the selected immunogenetic variants on 5-year metastases-free (5yrMFS), 5-year disease-free (5yrDFS), and 10-year overall (10yrOS) survival was tested in the entire Set of 370 patients. Results: Two immunogenetic IL17F ( IL17F -rs641701 and IL17F -rs9463772) markers predictive of 2yrRFS, 5yrDFS, 5yrMFS, and 10yrOS were identified. The combination of tumor regression grade (TRG) and patients genotype for IL17F -rs641701 and IL17F -rs9463772 allowed the identification of subgroups of patients with differential prognosis in term of both 5yrDFS (HR 11.29, P -value <0.001, and HR 5.86, P-value = 0.001, respectively) and 10yrOS (HR 7.07, P -value = 0.005, and HR 6.05, P -value = 0.002, respectively). Conclusion: IL17F -rs641701 and IL17F -rs9463772 were highlighted as promising immunogenetic markers significantly associated with the prognosis of LARC patients. After a prospective validation of the herein reported findings, the combination of TRG and patients genotype should be considered to provide additional stratification criteria for the selection of a personalized multimodality treatment.